2001
DOI: 10.1093/emboj/20.10.2357
|View full text |Cite
|
Sign up to set email alerts
|

26S proteasomes and immunoproteasomes produce mainly N-extended versions of an antigenic peptide

Abstract: Protein degradation by proteasomes is the source of most antigenic peptides presented on MHC class I molecules. To determine whether proteasomes generate these peptides directly or longer precursors, we developed new methods to measure the ef®ciency with which 26S and 20S particles, during degradation of a protein, generate the presented epitope or potential precursors. Breakdown of ovalbumin by the 26S and 20S proteasomes yielded the immunodominant peptide SIINFEKL, but produced primarily variants containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
255
1
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 297 publications
(274 citation statements)
references
References 43 publications
14
255
1
4
Order By: Relevance
“…Therefore, it is remarkable that when enolase was degraded with immunoproteasomes and constitutive proteasomes, approximately the same number of cleavage sites were observed (similar results were obtained for degradation of ovalalbumin Cascio et al 2001). One reason for this is that the immunoproteasome uses leucine, which is a very abundant amino acid, much more frequently than the constitutive proteasome.…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…Therefore, it is remarkable that when enolase was degraded with immunoproteasomes and constitutive proteasomes, approximately the same number of cleavage sites were observed (similar results were obtained for degradation of ovalalbumin Cascio et al 2001). One reason for this is that the immunoproteasome uses leucine, which is a very abundant amino acid, much more frequently than the constitutive proteasome.…”
Section: Resultssupporting
confidence: 57%
“…The cleavage occurs between the P1 and the P1 0 position (Berger and Schechter 1970). It has been suggested that the P1 position is the most important position determining cleavage (Altuvia and Margalit 2000;Cascio et al 2001), although the flanking region may also be important (Ossendorp et al 1996;Beekman et al 2000;Mo et al 2000). One way of analyzing such data is to calculate the information content at the cleavage site and in the region flanking the cleavage site.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations